Integration of Biomass Gasification and Hot Gas Cleaning Processes - Sergio Rapagna; Elisa Savuto; Andrea Di Carlo; Katia Gallucci; Ugo Foscolo Pier (Chemical Engineering Transactions, 2018)
In the near future, most of the world population will live in the developing countries, and it is plausible that biomass will be one of the main renewable energy sources of the future. Fluidized bed reactors should be the best solution to transform biomasses having different physical properties in energy and chemical vectors through gasification, due to its possibility to operate continuously, at high temperatures, and to utilize catalysts into the reactor and downstream of it, in order to reduce tar, NH3 etc. in the product gas. Catalytic filter candles are an innovative solution for hot gas cleaning & conditioning. It has been demonstrated that catalytic ceramic filters inserted in the freeboard of a fluidized bed gasifier, allow the complete removal of particulate by means of their anisotropic porous filtering structure, and furthermore act as catalyst to remove tar and ammonia, thanks to the Ni based catalyst contained into the filter itself (Rapagnà, Gallucci and Foscolo, 2017). To by-pass the preparation of the catalytic ceramic filters and to render the overall process more feasible in practice, ceramic filters filled with commercial steam reforming catalyst pellets have been located in the freeboard of a 0.1 m ID fluidized bed reactor, where olivine particles act as bed inventory. Experimental tests were carried out to check the values of the gas pressure drop through the plain filter and through the filter containing catalyst pellets, at different temperatures and gas filtration velocities. It has been found that at the highest temperature and filtration velocity (T 800°C and v 140 m/h) the pressure drops are around 48 mbar, while at the operating conditions (T 800°C and v 100 m/h) the total pressure drops are only 35 mbar. Furthermore it was observed that there is an almost negligible difference between the pressure drops in the case of empty and filled candle; it was thus deduced that the catalyst pellets do not cause relevant additional losses compared to the empty filter. The trends of pressure drops were fitted with the empirical Darcy-Forchheimer relation and with the Ergun equation, and it was found that the major contribution is given by the viscous term of the relation. Furthermore an additional contribution of concentrated pressure drops was identified and ascribed to the outer Al2O3 membrane of the candle characterized by very fine pores.